Association between interleukin-8 and severity of dengue shock syndrome in children - Suryadi N. N. Tatura; Dasril Daud; Irawan Yusuf; Sitti Wahyuni; Janno B. Bernadus (Indonesian Pediatric Society, 2016)
Background Dengue hemorrhagic fever (DHF) remains a major health problem in tropical countries. The case fatality rate (CFR) can be reduced from 45% to <1%, if dengue shock syndrome (DSS) is treated early and adequately. Early biomarkers for DSS outcomes in children are needed. Interleukin-8 (IL-8) might be one of the molecule, as it plays a role in the pathophysiology of DHF in children.Objective To assess IL-8 levels in pediatric DHF patients at various stages of illness severity and to determine the correlation between serum IL-8 concentration on admission and DSS outcomes in children.Methods A prospective cohort study was done in children with DSS who were admitted to the Pediatrics Department of Kandou Hospital, Manado. We measured subjects’ serum IL-8 levels at the time of DSS diagnosis and followed-up subjects until there was improvement or deterioration. An association between IL-8 and DSS outcome was analyzed using univariable logistic regression test. An ROC curve and Chi-square test were used to analyze the prognostic value of serum IL-8 levels. Statistical significance was considered to be a P value of <0.05 (power 80, β=0.20)..Results Fifty-eight children with DSS were included in this study. Twenty-seven subjects had clinical deterioration (to recurrent shock, prolonged shock or died). There was a significant association between elevated IL-8 levels and clinical deterioration in DSS (OR 116.7; 95%CI 18.0 to 756.0; P=0.0001). The ROC curve revealed an IL-8 cut-off level of 194.9 pg/mL, AUC 0.982, with sensitivity 89.3%, specificity 93.3%, positive predictive value (PPV) 92.6%, negative predictive value (NPV) 90.3%.Conclusion There is an association between elevated early serum IL-8 level and a DSS deterioration. Further prognostic studies are needed to confirm the predictive ability of serum IL-8 level on DSS deterioration in children.